Implementasi Akad Musyarakah Mutanaqisah di BNU’26 Syariah Magelang - Fadli, M. Robit Nailal; Purwanto, Purwanto; Fitriyani, Yeny; Pudail, M.; Labib, Achmad (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2024)
One of the obstacles in the Musyarakah Mutanaqisah contract is that two contracts must be carried out, namely cooperation (Syirkah) and rent (Ijarah). In implementing musyarakah mutanaqishah, two types of transactions are involved in one agreement. Therefore, capital goods are not only the object of transactions in musyarakah mutanaqishah but also function as objects in ijarah transactions for business development and as objects in buying and selling transactions to protect ownership of capital goods. This research aims to determine how the implementation of the musyarakah mutanaqisah contract at Bank BNU'26 Syariah Magelang is implemented. Mutanaqisah musyarakah contract is an agreement or arrangement between two or more people that is derivative and in the form of an agreement. This study uses qualitative methods with two approaches, namely interviews and observations. The results of this study confirm that BNU'26 Syariah, implementing the mutanaqisah musyarakah contract to customers, is there is cooperation between the bank and the customer in an effort based on mutual agreement. The contract can be agreed upon if the customer agrees to the requirements that Bank BNU'26 Syariah Magelang has determined.